English Reading Efficiency of Non-English-Major Students via Context Clues Reading Drills - Boonchum, Patumporn (Journal of Community Development Research (Humanities and Social Sciences); Vol 11 No 4 (2561): October-November 2018DO - 10.14456/jcdr-hs.2018.27, 2018)
English is an official language in the world and lots of students learn it for communicating with foreigners. Therefore, four English skills are necessary to learn. Also, reading skill is important for students to read English proficiently and this is the reason for the study. The purpose of the study was to investigate English reading efficiency of students who do not study English as their major before and after being taught through context clues English reading drills. The instruments used in this study were context clues English reading drills. T-test Paired Two Sample for Mean was carried out to test differences between pre-test and post-test, including testing hypothesis of the study. The research findings revealed that students’ English reading proficiency referred to the students’ scores of post-test was greater than pre-test significantly at .05 level after being instructed via the context clues English reading drills. The average score of the pre-test was 12.76 and the post-test was 16.17. Additionally, testing the hypothesis of the study was found that the value of t-Stat a 10.69 was greater than the value of t-Critical as 1.66. This indicates that the students’ English reading proficiency has developed when they learn through the drills. Keywords: English Reading Efficiency, Context Clues, English Reading Drills